2007
DOI: 10.1007/s11248-007-9131-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the carotenoid content of Brassica napus seeds by downregulating lycopene epsilon cyclase

Abstract: The accumulation of carotenoids in higher plants is regulated by the environment, tissue type and developmental stage. In Brassica napus leaves, beta-carotene and lutein were the main carotenoids present while petals primarily accumulated lutein and violaxanthin. Carotenoid accumulation in seeds was developmentally regulated with the highest levels detected at 35-40 days post anthesis. The carotenoid biosynthesis pathway branches after the formation of lycopene. One branch forms carotenoids with two beta rings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 50 publications
2
95
0
Order By: Relevance
“…A molecular synergism between eLCY and bLCY activities is an overall major determinant of flux through the branch leading to production of lutein, b-carotene and other xanthophylls cycle (XC) carotenoids ( Fig. 1) (Yu et al 2008;Bai et al 2009). Investigations have yielded mutants perturbing lutein biosynthesis including lut1, e-hydroxylase (Tian et al 2004); lut2, eLCY (Cunningham et al 1996;Pogson et al 1996); ccr2, CRTISO (Park et al 2002); and lut5, an additional b-hydroxylase (Kim and DellaPenna 2006) as well as the SDG8 chromatin regulatory mutant, ccr1 (Cazzonelli et al 2009a).…”
Section: Carotenoid Biosynthesis and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A molecular synergism between eLCY and bLCY activities is an overall major determinant of flux through the branch leading to production of lutein, b-carotene and other xanthophylls cycle (XC) carotenoids ( Fig. 1) (Yu et al 2008;Bai et al 2009). Investigations have yielded mutants perturbing lutein biosynthesis including lut1, e-hydroxylase (Tian et al 2004); lut2, eLCY (Cunningham et al 1996;Pogson et al 1996); ccr2, CRTISO (Park et al 2002); and lut5, an additional b-hydroxylase (Kim and DellaPenna 2006) as well as the SDG8 chromatin regulatory mutant, ccr1 (Cazzonelli et al 2009a).…”
Section: Carotenoid Biosynthesis and Regulationmentioning
confidence: 99%
“…3), revealing that feedback may partially explain the reduced lutein observed in ccr2 and ccr1 mutants (Cuttriss et al 2007;Cazzonelli et al 2009a). Further, a reduction in seed eLCY mRNA levels show higher total carotenoid content, specifically increased levels of b-carotene, zeaxanthin, violaxanthin and unexpectedly, lutein (Yu et al 2008). However, another report showed that tuber specific silencing of eLCY resulted in an expected increase in b-carotene levels in potato (Solanum tuberosum) (Diretto et al 2006).…”
Section: Carotenoid Signals and Metabolite Feedback Controlmentioning
confidence: 99%
“…The embryos of maize lcyB mutant have been shown to accumulate lycopene and δ-carotene, whereas the endosperm accumulates lycopene, δ-carotene, γ-carotene, and ε-carotene (Bai et al 2009); however, these carotenoids are almost absent in the wild type. The suppression of ε LCY expression by RNAi techniques in Brassica napus resulted in the increase of carotenoids and in the ratio of β-carotene to lutein (Yu et al 2008). In potato, tuber-specific silencing of ε LCY gene by introducing an antisense fragment of the gene caused an increase in β-carotene and zeaxanthin, although not in lutein (Diretto et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of β LCY, several unusual carotenes have been shown to accumulate in maize (Zea mays L.; Bai et al 2009). The suppression of ε LCY expression results in an increase in carotenoid content and the ratio of β-carotene to lutein in Brassica napus seed (Yu et al 2008). On the other hand, tuber-specific silencing of the ε LCY gene, by introducing an antisense fragment of the gene, increases β-carotene and zeaxanthin contents in potato tuber (Solanum tuberosum L.; Diretto et al 2006).…”
mentioning
confidence: 99%
“…Genes encoding lycopene β-cyclase (LCYb) and lycopene ε-cyclase (LCYe) are involved in the biosynthesis of β-carotene and α-carotene (9,10,27). Downregulation of LCYb leads to the accumulation of lycopene in ripe tomato fruits (19).…”
Section: Introductionmentioning
confidence: 99%